CIRP Summary Findings: CSUCI First-time Freshmen, Fall 2003 through Fall 2005: Number, Percent Response by Gender, and Total Responses for Students at Comparable Universities - J.E. Gonzalez::::::
The Cooperative Institutional Research Program (CIRP) freshmen survey is a national research study that is conducted by the Higher Education Research Institute (HERI) at the University of California, Los Angeles. CSUCI has participated in three administrations of the CIRP—Fall 2003, Fall 2004 and Fall 2005. At CSUCI, the CIRP is administered to students during Freshmen Summer Orientation. The data is this report was compiled from reports produced by HERI. Survey responses from first-time freshmen at four-year public universities are included in this report for comparison purposes.The Cooperative Institutional Research Program (CIRP) freshmen survey is a national research study that is conducted by the Higher Education Research Institute (HERI) at the University of California, Los Angeles. CSUCI has participated in three administrations of the CIRP—Fall 2003, Fall 2004 and Fall 2005. At CSUCI, the CIRP is administered to students during Freshmen Summer Orientation. The data is this report was compiled from reports produced by HERI. Survey responses from first-time freshmen at four-year public universities are included in this report for comparison purposes.